Psychosocial factors influencing adherence to medication therapy and a low-sodium diet in patients with heart failure: A systematic review - Ni Made Sridarmayanti; Tuti Herawati; Muhamad Adam (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Heart failure (HF) is a complex clinical syndrome with an increasing prevalence that contributes to decreased quality of life and increased mortality. Adherence to medication therapy and a low-sodium diet is a key component of HF management; however, patient adherence remains low. Various factors, including psychosocial aspects, influence this condition. Purpose: To identify and synthesize psychosocial factors that significantly influence adherence to medication therapy and a low-sodium diet in patients with heart failure based on the literature published between 2015 and 2025 Method: This systematic literature review was conducted in accordance with the PRISMA guidelines. A literature search was performed across six databases using the PICOT framework: PubMed, ProQuest, Scopus, EBSCOhost, SAGE, and ClinicalKey for Nursing. The quality of the articles was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Results: A total of 10 articles with a combined sample of 5.611 participants pant were analyzed. The results indicate that depression and anxiety are negative psychological predictors that reduce patients’ motivation and self-regulation regarding adherence. Depression emerged as the dominant factor associated with decreased medication adherence. Social factors, particularly social support, act as protective factors that improve treatment adherence. As a component of social support, family support specifically contributes to adherence to a low-sodium diet through a proxy adherence mechanism. Conclusion: Psychosocial factors influence adherence to therapy in patients with heart failure. Therefore, a holistic approach integrating psychosocial interventions is needed to optimize therapeutic adherence and improve clinical outcomes.